Pixels: Creating Lessons with Historical Connections Between Perimeter and Circumference - Harkness, Shelly Sheats; Noblitt, Bethany (Ohio Journal of School Mathematics, 2017)
When teachersplay the believing game (Elbow, 1986) while in-the-moment of teaching, they attempt to tease out the merit in students’ answers or comments that might, at first, seem incorrect. Retrospective analysis of video of classroom episodes can allow mathematics teachers to play the believing game after-the-moment of teaching. Within this narrative we share how playing the believing game while analyzing video led us to explore the merit of one student’s comment and the historical connections between circumference and perimeter. Additionally, we describe an activity that Beth created for students in a subsequent mathematics course in order to help preservice teachers see those historical connections.